A study of insider threat behaviour: developing a holistic insider threat model - Munshi, Asmaa Mahdi (Curtin University, 2013)
This study investigates the factors that influence the insider threat behaviour. The research aims to develop a holistic view of insider threat behaviour and ways to manage it. This research adopts an Explanatory Mixed Methods approach for the research process. Firstly, the researcher collects the quantitative data and then the qualitative data. In the first phase, the holistic insider threat model is developed; in the second phase, best practices are developed to manage the threat.